Relatório da Conferência Temática UGI - IGU “As Geografias da Paz”, Bolívia 2017 - Delgado Estrada, Juan Manuel (2021)
Geography has generally been accused of being useful especially in waging war. Rather, it can offer a wide range of contributions to peacebuilding and socio-territorial conflict resolution on various national or local scales. The “Geographies for Peace” of 2017 was a thematic conference of the International Geographical Union, whose objective was, if possible, from a transdisciplinary entry, its study, in this sense, from the historical point of view and the role of the activities that socially construct the space of “Peace” such as education, culture, politics, economy or tourism, because for the sociopolitical analysis of war and peace it is necessary to carry out this exercise of measuring power and its impact on the multiscale territory . To make this review or comment of the 2017 event, we consider it very relevant and current due to the situation in the midst of the Covid-19 pandemic on a global and local scale, which is a dispute between the state and the Sars Cov-2 virus of the territory through terror (territory) or territoriality / deterritoriality that reminds us of that liminality between Peace and War. Likewise, it makes us visible the importance of the academic events of the UGI and their influence on the geographical thinking of the countries receiving the event, the antecedents and the conjunctures that occur before, during or after events of these characteristics, possible Legacies and criticisms regarding this academic activity, such as the UGI Bolivia Thematic Conference 2017.